2020
DOI: 10.3390/ijms21082724
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Gene Profiling Reveals Social Status-Dependent Modulation of Nuclear Hormone Receptors in GnRH Neurons in a Male Cichlid Fish

Abstract: Gonadotropin-releasing hormone (GnRH) is essential for the initiation and maintenance of reproductive functions in vertebrates. To date, three distinct paralogue lineages, GnRH1, GnRH2, and GnRH3, have been identified with different functions and regulatory mechanisms. Among them, hypothalamic GnRH1 neurons are classically known as the hypophysiotropic form that is regulated by estrogen feedback. However, the mechanism of action underlying the estrogen-dependent regulation of GnRH1 has been debated, mainly due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 80 publications
1
9
0
Order By: Relevance
“…Ogawa and Parhar showed by single-cell gene pro ling that, although Arb mRNA as well as Tr, Gr, and Er mRNAs were expressed in GnRH3 neurons, the expression level of Arb mRNA was so low that nested-PCR was necessary to observe it. [29] Combining these results with ours, it can be proposed that the effect of 11-KT on GnRH3 neurons is mediated by other molecules such as IGF-1 and its receptor, although it cannot be completely ruled out that 11-KT affects GnRH3 neurons directly.…”
Section: Discussionsupporting
confidence: 68%
“…Ogawa and Parhar showed by single-cell gene pro ling that, although Arb mRNA as well as Tr, Gr, and Er mRNAs were expressed in GnRH3 neurons, the expression level of Arb mRNA was so low that nested-PCR was necessary to observe it. [29] Combining these results with ours, it can be proposed that the effect of 11-KT on GnRH3 neurons is mediated by other molecules such as IGF-1 and its receptor, although it cannot be completely ruled out that 11-KT affects GnRH3 neurons directly.…”
Section: Discussionsupporting
confidence: 68%
“…However, a few studies have reported the presence of Esrs and Ars in teleost Gnrh neurons, suggesting the possibility of a direct sex steroid feedback. The erα paralog was found to be expressed in Gnrh3 neurons in medaka ( 195 ) and in Gnrh1, 2, and 3 neurons in Nile tilapia ( 242 ), while both arα and arβ were found in Gnrh1 neurons in the cichlid Astatotilapia burtoni ( 179 ). Thus, it is possible that sex steroids might regulate Gnrh activity and proliferation directly in teleosts, although as described below there is more evidence of indirect pathways via effects on Gnrh regulatory factors (e.g., kisspeptin and dopamine), as seen in mammals.…”
Section: Sex Steroids Mediate Gonadotrope Plasticity Directly and mentioning
confidence: 99%
“…Single cell harvesting of GnRH-GAP-immunoreactive cells and total RNA extraction was performed as described previously with slight modifications ( 38 , 39 , 42 , 44 ). Briefly, the brain sections were immunoreacted with GAP antiserum for overnight followed by incubation with secondary antibodies (AlexaFluor 488- or 594-labeled anti-rabbit IgG) as described above in RNase-free buffer.…”
Section: Methodsmentioning
confidence: 99%